The Lullingstone Mosaic Inscription — A Parody of Martial?. (2nd May 2016) - Cosh, S.R.
ABSTRACT: The original poem inscribed above an image of Europa and the bull on the Lullingstone villa mosaic has long been recognised as referring to an episode in Ovid's Metamorphoses and making an allusion to Virgil's Aeneid . Here it is proposed that it is also a parody of a poem by Martial on the same subject and adds to the growing quantity of classical literature with which the fourth-century Romano-British elite are known to have been familiar.